Creative competences in the perspective of positive resources - Halina Wróblewska (Jan Dlugosz University, 2022)
The subject of the study are creative competences presented as the potential of subjective resources. It presents the issues of research questions, empirical verifications, and includes references and inspirations. The adopted perspective of development resources determines a positive model of human development. It fits in with the postulate of developing positive education, aimed at supporting human creative resources, building educational programs in a climate of pro-creativity and pro-capacity. The adopted positive resource perspective is part of the trend of positive pedagogy (positive development).